UMPSA celebrates 115 loyal staff members in Majlis Sanjungan Budi 2025 - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 14 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) honoured the service and dedication of 115 staff members who have devoted two decades of service to the university in Majlis Sanjugan Budi 2025, held in conjunction with the Vice-Chancellor’s Address Ceremony at the Multipurpose Hall, UMPSA Pekan.